Reproductive aspects of the spider crab Libinia dubia under laboratory conditions - Carmona-Osalde, Claudia; Rodríguez-Serna, Miguel (HIDROBIOLÓGICA, 2017)
The present study documents some aspects of the reproductive biology of the spider crab Libinia dubia (H. Milne Edwards, 1834) in conditions of captivity. Forty males and 43 ovigerous females were collected with traps and transported to the laboratory, where they were kept in seawater tanks. Average egg count per female was 20,637 (±SD 12,683.33), with an 81% (±SD 4.62) viability until hatching. Males were larger and heavier than females. On average, females measured 69 mm in length × 59 mm in width. The equation for the linear relationship between female weight (W) and number of eggs produced per female was: Y = -10,290.03 + 242.89 X (r2 = 0.866). Egg development at a temperature of 24 ± 1 °C occurred in five stages based on coloration: stage 1 (day 1-10), bright orange; stage 2 (day 11-24), orange; stage 3 (day 25-29), gray; stage 4 (day 30-34), light gray; and stage 5 (35-37), white, visible larvae. Females spawned at least twice and were receptive to males after each spawning event, although no spermatophore transfer was observed. The adaptive capacity of L. dubia to captivity makes its use feasible in breeding under controlled conditions, suggesting that it has potential for aquaculture.